(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2025)
The article examines the theoretical and methodological foundations of forming accounting information on bank credit operations within the framework of modern digital transformation processes in the financial sector. The study emphasizes the importance of developing an integrated accounting architecture that ensures the reliability, consistency, and analytical depth of credit-related data throughout the entire credit life cycle – from issuance to repayment or recognition as uncollectible. The proposed architectonics of accounting information arrangement provides a structured approach to recording, classifying, and analysing credit operations, which enhances the transparency of financial reporting and supports effective decision-making by banking institutions. This substantiates the need to integrate analytical modules into accounting systems to automate data processing and enable real-time monitoring of credit portfolios. Particular attention is paid to the harmonization of national accounting practices with international financial reporting standards (IFRS), that promote comparability, accuracy, and compliance in credit risk assessment. The implementation of digital visualization tools for credit flows is proposed as a means of improving reporting transparency, analytical efficiency, and stakeholder confidence. The study highlights the role of modern information technologies in the optimization of accounting processes and risk management in banking. It is argued that the formation of accounting information should be based on the principles of continuity, transparency, and analytical integrity, which are essential for ensuring the stability and credibility of the banking system. The results of the study can be used to develop methodological recommendations and digital tools aimed at improving the quality, reliability, and analytical potential of accounting information on credit operations in banks.